Methylphenidate attenuates the response to cold pain but not to aversive auditory stimuli in healthy human: a double-blind randomized controlled study. (May 2017) - Pud, Dorit; Broitman, Eelena; Hameed, Omar; Suzan, Erica; Aviram, Joshua; Haddad, May; Hadad, Salim; Shemesh, Rafi; Eisenberg, Elon
Abstract: Introduction: We recently showed that the psycho-stimulant norepinephrine–dopamine reuptake inhibitor methylphenidate (MP) prolonged cold pain threshold and tolerance in adults with attention-deficit hyperactivity disorder (ADHD). Objectives: The objectives of the present study were to: (1) examine whether MP has antinociceptive properties in healthy men; (2) test MP's effects on responses to aversive auditory stimuli. The underlying aim was to determine whether MP exerts antinociceptive properties or more generalized, nonspecific attenuating effects on different aversive sensory modalities. Methods: This double-blind, crossover, randomized placebo-controlled study consisted of 2 sessions one week apart from each other. In each session, pain threshold (seconds) and tolerance (seconds) in response to painful cold stimulation were measured. Additionally, threshold (dB) and tolerance (seconds) to loud aversive auditory stimuli (500 Hz, 2000 Hz and white noise) were also tested prior to and 2 hours following the administration of a single dose of either 20 mg MP or an identical looking placebo. Results: Forty men, 26.1 ± 4.0 (mean ± SD) years were enrolled in the study. Wilcoxon signed-rank test analyses showed that MP, but not the placebo, produced a significant increase in cold pain threshold (from 4.1 ± 2.6 to 5.4 ± 3.1 seconds, P = 0.001 and from 4.5 ± 2.6 to 4.3 ± 2.7 seconds, P = 0.2, respectively) and tolerance (from 57.8 ± 54.0 to 73.8 ± 61.8 seconds, P = 0.001 and from 52.5 ± 53.7 sec to 57.0 ± 52.9 seconds, P = 0.1, respectively). No significant changes were found in any of the auditory parameters. Conclusion: These results suggest that MP has an effect on nociceptive pathways rather than a nonspecific, generalized attenuating effect on aversive sensory stimuli. Abstract : This double-blind, crossover, randomized placebo-controlled study found that methylphenidate has a specific effect on nociceptive pathways rather than a generalized effect on aversive sensory modalities.